Apakah Kinerja Jangka Panjang Penawaran Umum Perdana Di Indonesia Underperformed? - Suherman, Suherman (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2016)
The objective of this research is to investigate the long-run performance of Indonesian Initial Public Offerings (IPOs). Sample of this research covers 101 IPO firms between 1999 and 2005 listed on Jakarta Stock Exchange. Sample is categorized into panel A (all IPOs sample), panel B (non-financial firm IPOs), panel C (non-privatized IPOs) and panel D (privatized IPOs).The results show that insignificant underperformance is found for EWCAR and VWCAR (except privatized IPOs showing insignificant outperformance), significant underperformance is found for EWBHAR (except privatized IPOs showing outperformance, although insignificant), and significant outperformance is found for VWBHAR (except privatized IPOs showing insignificant outperformance). The underperformance disappears, however, when calendar-time approach is utilized. The intercepts in Fama-French three-factor regressions are insignificantly different from zero, suggesting no abnormal performance.